Nutritional status and its associated factors among the elderly population of urban Puducherry - G., Praveena; R., Porkodi; J., Venkatachalam (International Journal Of Community Medicine And Public Health, 2024)
Background: Health of the elderly determines the wealth of the nation. The capacity to defend the body against disease, maintain anatomic and structural normality, cognitive function, and desire for social activity are all influenced by one’s nutritional status. Various age-related changes like physiological, psychological, social, nutritional, and environmental risk factors make the elderly vulnerable to malnutrition and increase the risk of impairment in vital functions of major organs. It is more complex in the elderly than in young age as it determines their morbidity and mortality. Methods: A cross-sectional analytical study among 250 elderly using a simple random sampling method. The nutritional status was assessed with a mini nutritional assessment scale and activities of daily living using the Lawton-Brody IADL scale. The data was analyzed using descriptive and inferential statistics at a 5% level of significance. Results: Among 250 elderly, only 68 (27.2%) of them had normal nutritional status and a majority 146 (58.4%) were at risk of malnutrition. More than half 130 (52%) of the elderly had mild anemia and only 85 (34%) of them had normal levels of hemoglobin. The education level, occupation, per capita income, type of stay, BMI, and functional level (p<0.001), while gender (p<0.01) and religion, and hemoglobin (p<0.05) had a significant association with the nutritional status of the elderly. Conclusions: The elderly at risk for malnutrition are more than those who are malnourished. Attention towards the elderly nutrition and associated morbidities needs focus by the family, health personnel and the government for the increasing population of the elderly.